Application of KoHeA+MF Compost at Various Dose of Inorganic Fertilizer to Increase Soil Fertility and Production of Hybrid Corn Seeds JH-37 - Wulantika, Trisia; Sondang, Yun; Sembiring, Ngakumalem; Hardaningsih, Wiwik; Wahono, Sentot; Fitri, Febria; Ariliusra, Azzukhruf; Harnas, Hafid (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2025)
Corn is one of the important food commodities after rice and wheat. Corn acts as a food, feed, and industrial ingredient. The need for corn in Limapuluh Kota Regency is very high along with the development of chicken farming businesses that require corn as the largest feed mixture. However, the need for corn has not been met by corn production in this Regency. The low corn production is more due to the low supply and use of superior corn seeds, as well as low soil fertility. One effort to increase soil fertility is the use of KoHeA+MF compost. The purpose of this study is to ascertain how the production of KoHeA+MF hybrid seeds is impacted by the dosage of KoHeA+MF compost and the quantity of inorganic fertilizer that can be substituted. The study was conducted from May to September 2024 at the seed production land of PT. AZUMA Situjuah, Limapuluh Kota Regency, West Sumatra. The study used a Randomized Block Design (RBD) with 5 treatments, including: 100% inorganic fertilizer (Control), 75% inorganic fertilizer + 10 tons/ha KoHeA+MF, 50% inorganic fertilizer + 10 tons/ha KoHeA+MF, 25% inorganic fertilizer + 10 tons/ha KoHeA+MF, and 0% inorganic fertilizer + 10 tons/ha KoHeA+MF.The application of various doses of inorganic fertilizer combined with 10 tons/ha KoHeA+MF affected soil fertility, especially the increase in soil pH (H2O), organic C, total N, P2O5, K2O, and soil Ca. The application of inorganic fertilizer + 10 tons/ha KoHeA+MF significantly affected vegetative growth, yield components and corn kernel production of JH37 corn. The optimal dosage for dry corn kernel production is 10 tons/ha of KoHeA+MF and 75% inorganic fertilizer.